olubility Enhancement for Dietheyldithiocarbamate-Zinc for Lung Cancer Treatment - Ayse Kaya; Niusha Ansari-Fard; Dan Alves; Basel Arafat; Havovi Chichger; Mohammad Najlah (University of Huddersfield Press, 2022)
Diethyldithiocarbamate zinc (Zn(DDC)2), has shown promising antineoplastic effects against a wide variety of cancers. However, this application was hindered by its poor water solubility. Therefore, complexation with cyclodextrin was used to enhance the solubility. Five different concentrations of 2-hydroxyl beta-cyclodextrin (HP) and ether beta-cyclodextrin (SBE) were used. CD-Zn(DDC)2 solutions were freez-dried for further characterisation using DSC, TGA and FT-IR. The phase solubility study showed a significant water-solubility enchantment of Zn(DDC)2, and the characterisation studies confirmed the formation of inclusion complexes CD-Zn(DDC)2. Overall, CDs have improved Zn(DDC)2 solubility significantly and showed a promising anticancer activity against lung cancer cells. Hence, CD-Zn(DDC)2 complexes have a great potential for further studies against cancer.